Pengaruh Store Atmosphere dan Experiential Marketing Terhadap Minat Beli dengan Kepuasan Konsumen Sebagai Pemediasi: Studi pada Warung Kopi Tropical Space - Khafifah Rahmasari; Idris Yanto Niode; Andi Juanna (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the Influence of Store Atmosphere and Experiential Marketing on Purchase Interest with Consumer Satisfaction as a Mediator at the Tropical Space Coffee Shop. The approach in this study is quantitative with a correlational method. Data collection in this study was carried out using a questionnaire. The number of samples was 75 people obtained through a saturated sampling process. Data analysis in this study was quantitative inferential path analysis. The results of the study show that (1) Store atmosphere has a positive and significant effect on consumer satisfaction at the Tropical Space coffee shop with a path coefficient of 28.60%. (2) Experiential marketing has a positive and significant effect on consumer satisfaction at the Tropical Space coffee shop with a path coefficient of 41.90%. (3) Store atmosphere has a positive and significant effect on consumer purchasing interest at the Tropical Space coffee shop with a path coefficient of 19.50%. (4) Experiential marketing has a positive but insignificant effect on consumer purchasing interest at the Tropical Space coffee shop with a path coefficient of 7.60%. (5) Consumer satisfaction has a positive and significant effect on consumer purchasing interest at the Tropical Space coffee shop with a path coefficient of 50.40%. (6) Store atmosphere through consumer satisfaction has a positive and significant effect on consumer purchasing interest at the Tropical Space coffee shop with a path coefficient of 33.90%. The results of a significant influence mean that consumer satisfaction is able to be a good intervening variable in increasing the influence of store atmosphere on consumer purchasing interest at the Tropical Space coffee shop. (7) Experiential marketing through consumer satisfaction has a positive and significant influence on consumer purchasing interest at the Tropical Space coffee shop with a path coefficient of 28.70%. The results of a significant influence mean that consumer satisfaction is able to be a good intervening variable in increasing the influence of experiential marketing on consumer purchasing interest at the Tropical Space coffee shop.